Endocannabinoid System and Ocular Vascularization - Iancu, Raluca; Coman, Ioana-Cristina; Barac, Cosmina; Al Hammoud, Mohammad; Popa Cherecheanu, Alina (Nepalese Journal of Ophthalmology, 2018)
The focus of this review is the role of endocannabinoid system in ocular and systemic circulation. By critically examining preclinical and clinical research, we explore the cannabinoid receptors localization and vascular implications as well as their interaction with other anti-inflammatory drugs. The objective is to transfer knowledge on the use of cannabinoids, specifically their effect on ocular circulation and intraocular pressure, and provide a better understanding of the endocannabinoid system complexity in modulating local and systemic circulations in order to identify potential uses and limitations of cannabinoid-based therapeutics.